2011
DOI: 10.1523/jneurosci.6209-10.2011
|View full text |Cite
|
Sign up to set email alerts
|

Distinct and Non-Redundant Roles of Microglia and Myeloid Subsets in Mouse Models of Alzheimer's Disease

Abstract: Mononuclear phagocytes are important modulators of Alzheimer's disease (AD), but the specific functions of resident microglia, bone marrow-derived mononuclear cells, and perivascular macrophages have not been resolved. To elucidate the spatiotemporal roles of mononuclear phagocytes during disease, we targeted myeloid cell subsets from different compartments and examined disease pathogenesis in three different mouse models of AD (APP swe/PS1 , APP swe , and APP23 mice). We identified chemokine receptor 2 (CCR2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
270
1
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 298 publications
(295 citation statements)
references
References 53 publications
20
270
1
4
Order By: Relevance
“…Blood-borne monocytes have been shown to infiltrate damaged or diseased brain tissue in animal models of other human neurological disease, such as the EAE model of multiple sclerosis (35), Alzheimer's disease (27,28,44), and traumatic brain injury (13,45). Previous studies have also reported elevated numbers of peripheral immune leukocytes after epileptiform activity (46,47).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Blood-borne monocytes have been shown to infiltrate damaged or diseased brain tissue in animal models of other human neurological disease, such as the EAE model of multiple sclerosis (35), Alzheimer's disease (27,28,44), and traumatic brain injury (13,45). Previous studies have also reported elevated numbers of peripheral immune leukocytes after epileptiform activity (46,47).…”
Section: Discussionmentioning
confidence: 99%
“…A subclass of circulating monocytes expresses high levels of CCR2 (25), whereas microglia lack CCR2 expression (11). Notably, Ccr2 knockout mice display reduced recruitment of circulating monocytes into inflamed tissues, including the brain, in injury and disease animal models, such as traumatic brain injury (13,26), EAE models (14,15), and Alzheimer's disease (27,28).…”
mentioning
confidence: 99%
“…Once activated, these cells can mediate progressive release of cytokines across the BBB and into the brain parenchyma (20). Finally, systemic administration of MPL may promote mobilization of microglial precursors from bone marrow, which move into the brain perivascular spaces and clear Aβ via phagocytosis (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…To obtain an infectivity-incubation time standard curve, 10-fold serial diluted brain homogenates used as the inocula of the Chandler and Obihiro strains were also injected into Tga 20 mice. The 50% lethal doses (LD 50 PrP-res detection by immunoblotting. For protease-resistant prion protein (PrP-res) detection, at 60, 90, and 120 dpi and at the terminal stage of the disease, brains were harvested and were homogenized in sterile PBS to prepare 10% (wt/vol) brain homogenates.…”
Section: Methodsmentioning
confidence: 99%
“…In AD model mice, bone marrow-derived microglia infiltrated from the peripheral circulation have protective potential against A␤ deposition and cognitive impairment in the early stage of the disease (47,48), although it is controversial whether the protective effect is due to a clearance of A␤ by microglia (49,50). However, it is also possible that at a later stage, increased A␤ production may overwhelm the microglial activity, or the proinflammatory milieu may decrease the phagocytic activity of microglia (51), or microglia may change the activation status to a more proinflammatory and neurotoxic phenotype (52).…”
Section: Prolonged Survival Of Prion-infected Cd14mentioning
confidence: 99%